Análise das sequências de genes marcadores evolutivos dos gêneros Prevotella e Megasphaera na classificação de organismos ruminais - Fabian, Elder Cavalcante (2021)
The search for improving the productive efficiency of the livestock activity, influenced both by the search to increase production in smaller areas and by the pressure to reduce environmental impacts, there is a growing need for us to have a better understanding of the processes that occur in the rumen environment. The present thesis aimed to carry out phylogenetic analyzes of ruminal bacterial genera in order to generate knowledge and allow a better understanding of the microbial communities present in this rich environment. For that, studies with phylogenetic analyzes were carried out using evolutionary marker genes of two genera with increasing importance in the study of ruminal microbiology, the Prevotella and Megasphaera genera. The first study showed that the presence of sequences of the 16S rRNA gene from non-cultured ruminal Prevotellas with a strong relationship with non-ruminal Prevotellas species indicated a common origin between these sequences and demonstrated that this environment facilitates the development of Prevotellas species with different substrate preferences fermentation. In addition, it was possible to verify that the uncultivated sequences of Prevotella sp. RML113, RML67, RML125, RML110 and NRCM B1 have a high probability of representing new species within the genus. In the second study it was found that the genus Megasphaera formed a clade deeply rooted with the monospecific genus Anaeroglobus, with the formation of at least three well-defined internal clusters within the genus. The findings of this work show that A. geminatus is not independent of the genus Megasphaera, forming with the other species of this genus a monophyletic branch supporting the proposition that A. geminatus should be reclassified as Megasphaera geminata comb. nov. It is concluded that the use of phylogenetic analyzes using evolutionary marker genes of ruminal microrganisms proves to be an efficient tool for a better understanding of the relationships that occur in the rumen microbial community and the factors that affect it.